2006
DOI: 10.1096/fj.06-5725fje
|View full text |Cite
|
Sign up to set email alerts
|

Human skin responses to UV radiation: pigment in the upper epidermis protects against DNA damage in the lower epidermis and facilitates apoptosis

Abstract: Melanin plays an important role in protecting the skin against UV radiation, and melanomas and basal/squamous cell carcinomas occur more frequently in individuals with fair/light skin. We previously reported that levels of melanin correlate inversely with amounts of DNA damage induced by UV in normal human skin of different racial/ethnic groups. We have now separately examined DNA damage in the upper and lower epidermal layers in various types of skin before and after exposure to UV and have measured subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
163
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(178 citation statements)
references
References 41 publications
13
163
0
2
Order By: Relevance
“…Cells were then incubated with primary antibodies overnight at 4°C, followed by incubation with Texas Red anti-rabbit or fluorescein isothiocyanate streptavidin for polyclonal and monoclonal antibodies, respectively (25). Human skin specimens embedded in paraffin were processed as described previously (26). Fluorescence signals were classified according to whether they showed green, red, or yellow fluorescence, the latter being indicative of colocalization of the red and green fluorescence signals.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were then incubated with primary antibodies overnight at 4°C, followed by incubation with Texas Red anti-rabbit or fluorescein isothiocyanate streptavidin for polyclonal and monoclonal antibodies, respectively (25). Human skin specimens embedded in paraffin were processed as described previously (26). Fluorescence signals were classified according to whether they showed green, red, or yellow fluorescence, the latter being indicative of colocalization of the red and green fluorescence signals.…”
Section: Methodsmentioning
confidence: 99%
“…5,6,[30][31][32][33] These findings complete and confirm previous data obtained using skin colour classification based on ethnic origin or racial criteria. 34 They also emphasize that more pigmented melanocytes from intermediate and tan skin types may be targeted by UVR.…”
Section: Dna Damage In Melanocytesmentioning
confidence: 99%
“…8 The importance of UVB-induced apoptotic cell death as a protective mechanism becomes evident by the fact that the reduced risk of dark-skinned individuals to develop skin cancer is, to a major part, due to facilitation of UVB-induced epidermal apoptosis by melanin. 9 In addition, the property …”
mentioning
confidence: 99%
“…8 The importance of UVB-induced apoptotic cell death as a protective mechanism becomes evident by the fact that the reduced risk of dark-skinned individuals to develop skin cancer is, to a major part, due to facilitation of UVB-induced epidermal apoptosis by melanin. 9 In addition, the property of several plant polyphenols to prevent UVB-induced skin carcinogenesis is also attributed to their ability to increase apoptosis in epidermal cells. 6 We have previously shown that UVB exposure of keratinocyte (KC) resulted in the activation of the aryl hydrocarbon receptor (AHR), 10 a ligand-activated transcription factor and central regulator of drug metabolism.…”
mentioning
confidence: 99%